Sistematización de la experiencia práctica de intervención del diseño de un programa de calidad de vida en el trabajo, para el área administrativa de una empresa de comida rápida en la ciudad de Quito, en el período enero-agosto del 2017. - Zambrano Cornejo, Ligia Elena (2018)
This project is focused in designing a strategy of quality of life in work areas. Its goal is to offer the proper environment with better work conditions as well as equilibrium in the personal and work life of every staff member. This can be reached through certain activities emphasized in this proposal that will make it possible for workers to raise the commitment and satisfaction, which will also magnify the productivity in their tasks. In other words, an optimal life quality endeavors to achieve for happier and highly motivated workers who are to a greater extend connected to their duties in their work areas. Nowadays there are many organizations whose purpose is the wellbeing of their workers; however, only very few companies come out with successful strategies to make this happen. Nevertheless, if we really want to have the best teamwork and keep employees in the company, corporations must be aware of the needs of each member of their staff, not only in the professional angle but in the personal aspect too. This is the most effective way to achieve more committed, prompted and loyal workers with their occupations as well as with themselves. A poor quality of life in a line of work can lead to frustration, sadness, anger, stress, which ends with health issues that are generated by the unfavorable conditions of a daily work routine. Therefore, one of the biggest challenges for many organizations is to find the proper balance and welfare for their employees that will successfully enhance both, the personal and occupation ends, which depend not only of technological factors or the position the corporation has in the market but of the human capital.